Pengaruh Strategi Contextual Teaching And Learning Dan Motivasi Belajar Terhadap Hasil Belajar Siswa SD - Soritua Siregar Pahu; Ayi Darmana; Ucu Rahayu (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
This study aims to determine the effect of the interaction of CTL learning strategies and motivation on student learning outcomes on living things and their environment. This research was conducted at SD Negeri 02 Rantau Selatan, Labuhanbatu Regency. The instruments used were tests and questionnaires on learning motivation. The test instruments consist of 9 items of multiple choice, 9 items of essay test and 42 items of questionnaire. All instruments have been validated. The study used a quasi-experimental method with a 2 x 2 factorial design. The data analysis technique used ANOVA at the significance level α = 0.05. The results showed that student learning outcomes on living things and their environment materials taught using the CTL strategy were higher than student learning outcomes on living things and their environment taught using the Direct model Fcount  58.508 > Ftable  4.12, there is a difference. There is a significant difference between student learning outcomes in the material of living things and their environment that has high learning motivation with students who have low learning motivation Fcount  13.396 > Ftable  4.12, there is an interaction between learning strategies and learning motivation on student learning outcomes in the material living things and their environment Fcount 23.053 > Ftable 4.12. The results of the study can be concluded that the CTL strategy is better than direct learning. The CTL strategy is better used to teach students who have high learning motivation while direct learning is better used for students who have low learning motivation.